Designing an Impact Fee Program to Meet Rational Nexus Principle and Reduce Vertical Inequity: Key Insights for Developing Countries. (October 2016) - Mathur, Shishir
This article reviews three impact fee programs spread across three continents (North America, Australia, and Asia) in a search for those impact fee design features that meet the nexus and rough proportionality principles and promote vertical equity. To meet the nexus and rough proportionality principles, we assert that the impact fee should vary by use, intensity of use, and type of infrastructure or service funded by the fee, and that the fee should be based on clearly articulated service standards. Finally, specific policies that may be used to increase vertical equity include (a) allowing developers to pay the fee in installments and/or at a later stage of project development, (b) granting impact fee waivers for affordable housing, and (c) exempting smaller properties from paying the fee.